Some Ecological Studies on Hopea Odorata Roxb. and Hopea Pubescens Ridl. Seedlings - Phothisat, Saysamone (1998)
In Malaysia, Hopea odorata Roxb. and Hopea pubescens Rid!. have the local names of Me raw an siput jantan and Merawan bunga, respectively; while in Laos, their local names are Mai khen heua and Mai khen respectively. H. odorata is fairly widely distributed in evergreen forests from mainland Southeast Asia to the Andamand Islands, Borneo and the Philippine Islands, while H. pubescens is only endemic to Peninsular Malaysia. Both species belong to the Dipterocarpaceae, and are commercially important timbers. This project initially focused on the density, distribution, response to light of seedlings under forest canopy, seedling mortality and growth of H. pubescens. The project then focused on the influence of seed size on cumulative percentage germination and early growth of H. odorata seedlings under different light regimes in the nursery. The highest seedling density of H. pubescens was found to be 130 trees/subplot (of 25 m2) and the highest density of saplings was 68 trees/subplot. The distribution of seedlings and saplings was most abundant within 10m around the parent tree and no seedlings and saplings were found beyond 25m. The light intensity in the forest fluctuated according to the canopy opening. The highest light intensity recorded in the forest was 45.8%RLI and lowest at 3.0%RLI. The mortality of seedlings and saplings was quite high up to 12.9% and 5.3%, respectively and high mortality occurred in areas of high seedling density and where the light was low. In Plot 1, the mean annual increment in diameter (MAID) of all saplings was 0.37±0.2mm and the mean annual increment in height (MAIH) was 2.36±3.2cm. In Plot 2, the MAID of all saplings was 0.22±0.18mm and the MAIH was 3.02±4.29cm. Height and diameter increments of saplings in the forest were lower than increments recorded in the nursery.